2012
DOI: 10.1155/2012/286216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saponins against ClinicalE. coliStrains and Eukaryotic Cell Line

Abstract: Saponins are detergent-like substances showing antibacterial as well as anticancer potential. In this study, the effects of saponins from Quillaja saponaria were analyzed against prokaryotic and eukaryotic cells. Multidrug-resistant clinical E. coli strains were isolated from human urine. As eukaryotic cells, the CHO-K1 cell lines were applied. Antibacterial effect of ampicillin, streptomycin, and ciprofloxacin in the presence of saponins was measured by cultivation methods. Properties of saponins against CHO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 17 publications
9
60
0
8
Order By: Relevance
“…The results of our experiment showed that gentamicin decreased the dose of T. terrestris, so it had a synergistic effects with gentamicin. The synergistic effects of saponins with amphotericin B, itraconazole [31], mancozeb [32], and vancomycin [33] were confirmed, while saponins had no synergistic effects with ampicillin, streptomycin and ciprofloxacin against clinical isolates [27]. The synergy between T. terrestris methanol extract and gentamicin were confirmed by two methods in this study and are reported for the first time.…”
Section: Antibacterial Activity Of Tribulus Terrestris Methanol Extrasupporting
confidence: 65%
See 1 more Smart Citation
“…The results of our experiment showed that gentamicin decreased the dose of T. terrestris, so it had a synergistic effects with gentamicin. The synergistic effects of saponins with amphotericin B, itraconazole [31], mancozeb [32], and vancomycin [33] were confirmed, while saponins had no synergistic effects with ampicillin, streptomycin and ciprofloxacin against clinical isolates [27]. The synergy between T. terrestris methanol extract and gentamicin were confirmed by two methods in this study and are reported for the first time.…”
Section: Antibacterial Activity Of Tribulus Terrestris Methanol Extrasupporting
confidence: 65%
“…Saponins are detergent like substance and with surface active properties may disturb the bacterial membrane cells of bacteria [26]. Although, our result showed that T. terrestris containing a lot of saponins exhibited the high antibacterial activity against clinical isolates of E. coli, but saponins from Quillaja saponaria enhanced the growth of E. coli strains via increasing the influx of nutrients from medium into E. coli cells [27]. Indeed, the biological activity of saponins depended on the nature of their aglycone structure and the number of their sugars [28].…”
Section: Antibacterial Activity Of Tribulus Terrestris Methanol Extramentioning
confidence: 59%
“…Other studies also showed that glycyrrhetinic acid (aglycone of the saponin glycyrrhizin from liquorice roots) used in the treatment of gastric ulcer had bacteriostatic effects (Hostettmann and others ), while medicagenic acid (aglycone of alfalfa saponin) was reported to be bacteriostatic against Trichoderma viride (Lu and others ). Arabski and others () reported that the activity of Quillaja saponin was bactericidal against all tested strains of STEC at 37 °C within 1 h. Other bioactives like tannins and polyphenols present in QE could also contribute to the antibacterial activity of the extract used in this study. Therefore, it remains essential to evaluate the activity of individual bioactive components of commercial QE to understand the primary components responsible for the antibacterial activity of the extract.…”
Section: Resultsmentioning
confidence: 66%
“…Treatment of bacterial strains with QE : Cultures of the 4 E. coli O157:H7 and 6 non‐O157 STECs were grown overnight in Tryptic Soy Broth at 37 °C (TSB, Difco, Becton Dickinson). One milliliter of the homogenous bacterial culture was centrifuged for 3 min at 5000 × g to obtain a pellet which was then washed twice and resuspended in phosphate‐buffered saline (PBS, Difco, Becton Dickinson; pH 7.2), diluted 1:10 with PBS and treated with equal amounts of filter sterilized commercially available undiluted QE (pH 3.75) (obtained as a gift from Desert King, San Diego, Calif., U.S.A.) or PBS (untreated control) for 6 h or 16 h at room temperature (longer times were used compared to those at 37 °C, since initial studies did not show any reduction after shorter periods at RT) or for up to 1 h at 37 °C (Arabski and others ; Su and others ). The commercially available QE has a pH of 3.75 and contains sodium benzoate (0.1% w/w).…”
Section: Methodsmentioning
confidence: 99%
“…These chemical substances have antibacterial properties and have been proved in the previous studies. [3][4][5][6][7][8] If Pulsatilla chinensis proved to have antibacterial effect on pathogenic intestinal bacteria, it is not just provide a new alternative treatment for diarrhea and dysentery, but also for other intestinal infectious diseases. This study aimed to determine the antibacterial effect of P. chinensis towards staphlococcus aureus, Shigella dysenteriae, and Salmonella typhi.…”
Section: Introductionmentioning
confidence: 99%